Transforming Character Through Dhuha Prayers in Indonesian Education - Pradana, Adi Yudha; Istikomah, Istikomah (Indonesian Journal of Islamic Studies, 2024)
General Background: Education in Indonesia confronts a myriad of challenges, including regulatory frameworks, funding issues, and diverse implementation systems, which have led to concerns regarding the competitiveness of graduates in the global arena. Specific Background: One critical aspect of education involves character development among students, particularly in the context of the digital era. Knowledge Gap: While various educational interventions exist, the impact of religious practices, specifically the habituation of congregational dhuha prayers, on student character has not been extensively studied. Aims: This study aims to analyze the effect of habituating congregational dhuha prayers at SD Islam Al-Huda in Kediri on the character development of students. Results: Utilizing a qualitative approach through observation, documentation, and interviews, the findings reveal that this religious practice positively influences students' attitudes and discipline. Novelty: The research contributes to the literature by demonstrating that religious-based interventions can effectively enhance moral character in educational settings. Implications: These results suggest that integrating religious practices like dhuha prayers in school routines can be a valuable strategy for character education, offering practical insights for educators and policymakers seeking to foster holistic student development in Indonesia. Highlights: Dhuha prayers improve character development and student discipline. Qualitative methods provide comprehensive insights through observations and interviews. Religious practices enhance character education in schools effectively. Keywords: Dhuha prayers, character development, Islamic education, qualitative research, student discipline